Inclusive education in the Barents region - Tatiana V. Kuzmicheva (Высшее образование в России)
The article presents the analysis of the modern state of inclusive education practice in theBarents region taking into account the Russian and international experience in inclusion implementation. The structure of the regional model of psychological and pedagogical supportof children with limited health abilities and children with special educational needs is described.